Towards developing innovation management framework (IMF) for ICT organizations at Pakistan - Eram Abbasi; Imran Amin; Shama Siddiqui (Journal of Innovation and Entrepreneurship, 2022)
Various aspects of innovation management have been discussed in literature over the past few decades. Most of the innovation management frameworks have been formulated by undertaking studies in the developed world and lack the industry/culture specific focus. In this paper, we revisit the generic innovation management studies to develop an innovation management framework for highlighting the factors affecting innovation specifically at the Information Communication Technology (ICT) sector of Pakistan. A detailed literature review has been conducted to identify the factors included in the past innovation management models. To identify the factors specific for Pakistan, senior-level professionals, working at the Pakistani ICT organizations were interviewed based on a survey. A comparative analysis of the innovation management frameworks for Pakistan against those previously found in literature revealed interesting similarities and differences. Based on the study findings, an innovation management framework is developed that highlights the present factors which are important for innovation in the ICT sector for Pakistan. This framework can be used by Pakistan and other underdeveloped countries for improving their innovation in ICT sectors in particular and other sectors in general.
Keywords: 650; Framework; ICT; Innovation; Innovation management